The Effect of Deferred Tax Expenses, Profitability, Leverage and Company Size on Profit Management in Automotive Sector Companies on the Indonesia Stock Exchange - Khanza Taurin Kuncahyo; Ariyani (Journal of World Conference (JWC), 2023)
This study aims to analyze the effect of deferred tax expense, profitability, leverage and company size on earnings management in automotive sector companies on the Indonesia Stock Exchange. The sample for this study used automotive companies that were registered on the Indonesia Stock Exchange for 2017 – 2021. The sampling technique in this study used a purposive sampling technique that met the criteria determined by the researchers according to the research objectives. The type of data in this study uses quantitative data types and data sources in this study use secondary data sources. Secondary data related to this research uses documentary data in the form of automotive company financial reports for the period 2017 – 2021 sourced from the Indonesia Stock Exchange (IDX). The results of testing the first hypothesis (H1) show that deferred tax expense has no effect on earnings management. The results of testing the second hypothesis (H2) show that profitability has an effect on earnings management. The results of testing the third hypothesis (H3) show that leverage has an effect on earnings management. The results of testing the fourth hypothesis (H4) show that firm size has no effect on earnings management and the results of testing the fifth hypothesis (H5) indicate that deferred tax expense, profitability, leverage and company size have an effect on Earnings Management. The data obtained is in the form of financial reports from automotive companies listed on the Indonesia Stock Exchange website at www.idx.co.id and the period used in this study is 5 years in 2017-2021. This research is expected to be a reference for companies related to earnings management, companies can pay more attention to how to analyze the company and know the good and bad conditions of the company so that it can reflect good work performance for stakeholders. This Paper is Original Research paper